At the edge of the universe - Hutchinson, Shaun David (Simon Pulse, 2017)
When his best friend-turned-boyfriend goes missing and seems to be remembered by nobody else, Ozzie begins to believe that the universe is shrinking and forges ties with a new friend while struggling to figure out what is happening.